Trends of primary Schools’ Conflict Resolution as Peace Education: A Bibliometric Analysis - Wahyuningsih, Yona; Maftuh, Bunyamin; Sapriya, Sapriya; Darmawan, Deni (Universitas Jambi, Indonesia, 2024)
This research aimed to analyze computational mapping on bibliometric data